Under the Shadow of the Regime: The Contradictions of Policing in Sudan, c.1924-1989 - BERRIDGE, WILLIAM,JAMES (2011)
This thesis analyzes the institutional development of the Sudanese police between 1924 and 1989, focusing in particular on its role in governing Sudanese society and its relationship with the state at large. It seeks to challenge the static picture which represents the police as servile tools of ruling colonial and post-colonial regimes in Africa and a simple extension of the political executive. It contends that the police cannot be understood as the passive tools of the state, since both colonial and post-colonial states have been highly divided. The competing factions included legal and professional groups that wanted to develop a strong, united and institutionalized police force so as to exercise a systematic governance of Sudanese society, and political and administrative factions that sought to make the police serve the narrower political agendas of the regime. Central ruling factions, such as the Sudan Political Service in the colonial era and the military in the post-colonial era, have often seen a strong and institutionalized police force as a potential threat to their status, and have thus sought to weaken the police by conferring police authority to a number of parallel bodies. It will be seen that this conflict at the centre of the state helped to exacerbate the rift between the urban core and rural peripheries, as the various colonial and post-colonial governments sought to prevent the development of a united police force by dividing it along regional lines – and that the police came to serve, in some respects, as the state’s tools for enforcing this divide. Yet at the same time the thesis will seek to rehabilitate the police as actors within their own right, demonstrating the agency they exercised both as an institution and on behalf of various religious, ethnic and political groups to which they were affiliated